The Results of Pancreatic Resections and Long-Term Survival for Pancreatic Ductal Adenocarcinoma: A Single-Institution Experience. (March 2017) - Seppänen, H.; Juuti, A.; Mustonen, H.; Haapamäki, C.; Nordling, S.; Carpelan-Holmström, M.; Sirén, J.; Luettges, J.; Haglund, C.; Kiviluoto, T.
Objectives: Since the early 1990s, low long-term survival rates following pancreatic surgery for pancreatic ductal adenocarcinoma have challenged us to improve treatment. In this series, we aim to show improved survival from pancreatic ductal adenocarcinoma during the era of centralized pancreatic surgery. Methods: Analysis of all pancreatic resections performed at Helsinki University Hospital and survival of pancreatic ductal adenocarcinoma patients during 2000–2013 were included. Post-operative complications such as fistulas, reoperations, and mortality rates were recorded. Patient and tumor characteristics were compared with survival data. Results: Of the 853 patients undergoing pancreatic surgery, 581 (68%) were pancreaticoduodenectomies, 195 (21%) distal resections, 28 (3%) total pancreatectomies, and 49 (6%) other procedures. Mortality after pancreaticoduodenectomy was 2.1%. The clinically relevant B/C fistula rate was 7% after pancreaticoduodenectomy and 13% after distal resection, and the re-operation rate was 5%. The 5- and 10-year survival rates for pancreatic ductal adenocarcinoma were 22% and 14%; for T1-2, N0 and R0 tumors, the corresponding survival rates were 49% and 31%. Carbohydrate antigen 19-9 >75 kU/L, carcinoembryonic antigen >5 µg/L, N1, lymph-node ratio >20%, R1, and lack of adjuvant therapy were independent risk factors for decreased survival. Conclusion: After centralization of pancreatic surgery in southern Finland, we have managed to enable pancreatic ductal adenocarcinoma patients to survive markedly longer than in the early 1990s. Based on a 1.7-million population in our clinic, mortality rates are equal to those of other high-volume centers and long-term survival rates for pancreatic ductal adenocarcinoma have now risen to some of the highest reported.